Hyers–Ulam stability of non-autonomous and nonsingular delay difference equations - Rahmat, Gul; Ullah, Atta; Rahman, Aziz Ur; Sarwar, Muhammad; Abdeljawad, Thabet; Mukheimer, Aiman (Advances in difference equations, 2021)
In this paper, we study the uniqueness and existence of the solution of a non-autonomous and nonsingular delay difference equation using the well-known principle of contraction from fixed point theory. Furthermore, we study the Hyers–Ulam stability of the given system on a bounded discrete interval and then on an unbounded interval. An example is also given at the end to illustrate the theoretical work.